The Effect of English Song on Students’ Motivation in Learning English at SMP Negeri 8 Gunungsitoli - Fetry Shelvian Zebua; Yasminar Amaerita Telaumbanua; Yaredi Waruwu; Riswan Zega (Jurnal Ragam Pengabdian, 2026)
This study investigates the effect of using English songs on students' motivation in learning English at SMP Negeri 8 Gunungsitoli. Motivation plays an essential role in successful language learning, and integrating music as a medium is a creative strategy aligned with educational regulations to create engaging learning environments. The research employs a quantitative quasi- experimental design with a control and experimental group. Data were collected using questionnaires based on self-determination theory, focusing on students' autonomy, competence, and relatedness. Results indicate that the use of English songs significantly increases students' intrinsic motivation, enhancing their enthusiasm, confidence, and active participation in English learning activities. The results suggest that incorporating music into lessons can be an effective educational tool to foster motivation and improve language proficiency for junior high students. Relevant implications for teachers and educational institutions are discussed to optimize teaching strategies and learning outcomes.